Strategic and Operational Possibilities of Application of Expert Geological-Economic Evaluation of Mineral Reserves in the Conditions of the New Reality of Mineral Production - Tošović, Radule (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
Mineral production of various metallic, non-metallic and energy mineral raw materials belongs to geological, mining, technological, economic, ecological and health complex forms of material production, which suffers from different types of classical and non-classical influencing factors. The variability, especially of the external conditions of mineral production, with large and atypical changes in the existing state, and in the mineral sector, leads to the transition of abnormalities to a new state, which, in case of long duration, becomes normal and usual environment of mineral production. In the subject change of the production environment, the basic problem is the perception, identification and quantification of the changes made and their impact on the development, materially and economically, of successful mineral production in the companies of the mineral sector. The main goal is to provide favorable business conditions for companies engaged in the production of mineral resources, despite the manifested effect of unexpected and atypical external influencing factors on the production in question. In collecting the necessary data and information, methodically and practically special possibilities are opened by the application of the method of expert geological-economic evaluation of mineral reserves and mineral deposits. The method of expert geological-economic evaluation, with the accompanying use of the method of comparative analysis, becomes an important strategic, operational and modern tool for complex baseline analysis, preparation, adoption and implementation of important decisions in mineral production in the new business and production environment.